2010
DOI: 10.1371/journal.pone.0009104
|View full text |Cite
|
Sign up to set email alerts
|

SRRM2, a Potential Blood Biomarker Revealing High Alternative Splicing in Parkinson's Disease

Abstract: BackgroundParkinson's disease (PD) is a progressive neurodegenerative disorder that affects about five million people worldwide. Diagnosis remains clinical, based on phenotypic patterns. The discovery of laboratory markers that will enhance diagnostic accuracy, allow pre-clinical detection and tracking of disease progression is critically needed. These biomarkers may include transcripts with different isoforms.Methodology/Principal FindingsWe performed extensive analysis on 3 PD microarray experiments availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 38 publications
3
107
1
Order By: Relevance
“…Two criteria were used to determine whether a gene was differentially expressed: fold change of Ϯ1.2 and P value Ͻ 0.05 (using a two-tailed distribution). The value of 1.2 is an accepted cutoff which, with statistical significance, is likely to be validated by real-time PCR (28). Gene ontology and cluster analysis was performed by the use of the dChip software tool.…”
Section: Methodsmentioning
confidence: 99%
“…Two criteria were used to determine whether a gene was differentially expressed: fold change of Ϯ1.2 and P value Ͻ 0.05 (using a two-tailed distribution). The value of 1.2 is an accepted cutoff which, with statistical significance, is likely to be validated by real-time PCR (28). Gene ontology and cluster analysis was performed by the use of the dChip software tool.…”
Section: Methodsmentioning
confidence: 99%
“…As a new hallmark of cancer, AS has been involved in multiple oncological processes, including angiogenesis,1 invasion and metastasis,2 immune destruction3 and cellular energetics 45.…”
Section: Introductionmentioning
confidence: 99%
“…heat shock proteins and their chaperones), the autophagy processes, inflammation, adenosine receptors (caffeine) as well as oxidative metabolism (Table 1). In addition, in many of the postmortem studies found a link between familial to sporadic PD, with the finding of alterations in the transcription of SNCA [6,8,9,12], which may point to a common neurodegeneration mechanism in both cases. Similarly, UCHL-1 (PARK5) and DJ-1 (PARK7) mRNA were found to alter in sporadic PD [4][5][6]10].…”
Section: Introductionmentioning
confidence: 99%